O processo de trabalho dos caminhoneiros empregados do transporte rodoviário de cargas na formação histórica do Brasil e sua condição de proletariado - Kapron, Rafael Antônio (2021)
This thesis develops an elaboration on the work of Brazilian employed truck/truck drivers, focusing on their working conditions and labor relations in a period that extends from the 1970s to the 2010s. Through the uses of primary sources and bibliographical, with researches in different collections, physical sources and researches through the modern resources made available on the Internet, having as reference the category of the work process. Based on this, the peculiarities of Brazilian Road Cargo Transport are formulated, as a value of work, in its insertion in the global process of capitalist production, in the institutional structuring, in the size and business costs as trucks and in the workforce. With problematizations about the possibilities of quantification, the division of labor and the relationships between companies in the economic process, with the specificities of the productive capacities and salaries of drivers in the labor market, the determination of working hours, related to the other tasks assigned to professionals in relation to the duration in hours of work and the organization of work in the aspects of autonomy, control, discipline and training of workers that express a productive restructuring, accentuated from the 1990s onwards. In addition to determining the elements that define in professional practice during the workdays, issues such as the high incidence of occupational accidents, health problems and problems of insecurity in the determination of wage prices are exposed as recurring conditions throughout professional historical development. The thesis seeks to contribute to the historiography of labor and brazilian workers, analyzing a profession in the transport industry, determining the distinction between self-employed and employed drivers and elaborating on the conditions of the existence of piece wages and of time wages of drivers employed in the particularities of economic and political development, recording their status as a proletariat.